Teach yourself visually Python - Hart-Davis, Guy; Hart-Davis, Ted (John Wiley & Sons, 2022)
A simple, straightforward, and hands-on roadmap to the world of computer programming with Python Teach Yourself VISUALLY: Python is your personal guide to getting you started in programming. As one of the world's most popular--and most accessible--coding languages, Python is your gateway into the wide and wonderful world of computer science. This hands-on guide walks you through Python step by clearly illustrated step, from writing your very first Python code in a terminal window or the VS Code app through to creating your own lists, dictionaries, and custom classes. In the book, you'll learn to: Install Python and the tools you need to work with it on Windows, macOS, and Linux Work with files and folders, manipulate text, and create powerful functions that do exactly what you want Write clean code that makes decisions effectively, repeats actions as needed, and handles any errors that occur A must-have resource for aspiring programmers starting from the very beginning, Teach Yourself VISUALLY: Python is also an indispensable handbook for programmers making a transition from another language.
Includes index
Keywords: Python (Computer program language); Computer programming; Python (Langage de programmation); Programmation (Informatique); computer programming; handbooks; Handbooks and manuals; Instructional and education works; Guides et manuels